On the essence and ontology of systems - Perez, Gustavo De Jesus (Open Science Journal, 2020)
In the first part of this research, publications were reviewed from 1968 to 2019, with the aim of observing how the definition of system has evolved, since it was established by Ludwig Von Bertalanffy. From this review it is concluded that this definition has not changed in essence, all the researchers consulted use concepts similar to those of Bertalanffy, when they propose a definition of system. However, according to the specific field of work, the authors add their own characteristics. Bertalanffy's definition and all that have been derived from it postulate that a system is a conglomerate of interacting components. But after a brief reasoning it is concluded that everything in our universe meets that definition. A system is an atom, a cell, a chair, a galaxy, or the universe as a whole. So systems theory would be the theory of everything, which is too broad and imprecise. Vagueness and imprecision have been eliminated when the concept of system has been applied to specific fields of knowledge and human activity and in each of them characteristics have been added that define more specifically the systems that are relevant to certain technical or scientific specialties. However, this has caused that many concepts developed in one field cannot be extended or used in others. In this work, a system definition is established that allows us to clearly and precisely describe what these entities are and distinguish them from other concepts and entities. In this way it has been possible to characterize what a system is, using concepts that are applicable to any of the types of systems that can be found in our known world: natural systems, man-made systems and social systems.